FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN SEKTOR MANUFAKTUR - Andreanto Chandra; Dewi Kurnia Indrastuti (E-Jurnal Akuntansi TSM, 2022)
This study aims to analyze what factors affect audit report lag. These factors consist of profitability, auditor opinion, auditor switching, complexity, company reputation, board of size of directors, company size, and leverage as independent variables in this study. Meanwhile, audit report lag is the dependent variable in this study. Samples were taken from manufacturing firms listed on Indonesia Stock Exchange for year 2018-2020 using the purposive sampling method. Based on this, 234 research data meet the criteria as samples in this study. The result of this study is that profitability and leverage significantly positively affect audit report lag. Auditor switching, complexity, company reputation, board of size of directors, and company size have no effect on audit report lag.